Historical Accounts of the Indonesian 16th-Century Music Road - Bramantyo, Triyono; Suryati, Suryati (Harmonia: Journal of Arts Research and Education, 2023)
This research aims to seek clarity from a historical perspective to trace back the transmission and the remains of Gregorian chants in eastern Indonesia. This study also seeks clarity from a historical perspective to trace back the Indonesian situation prior to the arrival of the Portuguese. The Madjapahit Empire (1293-c1520) dominated historical events as the first attempts to unify the country. The research method employed in this study was a critical historical method to analyze treatises of Gregorian chants in eastern Indonesia, with the remains still being found today and known as the Holy Friday Procession in the islands of Flores. Under Gadjahmada’s hands, an ordinary-ranking officer who succeeded in becoming prime minister (Mahapatih) of the Madjapahit kingdom, the initial attempt at pan-Indonesia was successful, but the whole history of united Indonesia was dramatically declined by the death of Gadjahmada and since then united Indonesia was collapsed. When the Portuguese arrived in Indonesia, followed by the Dutch, British, and Japanese, there was no such single authority in Indonesia. The foreign powers trickily, exacerbated the situation and transformed themselves to strengthen their stronghold as occupiers. This important historical event was not known by the people of Indonesia in general and by the Indonesian historian in particular. Therefore, this research is more important to be done today than later.